Fine tuning the structural colours of photonic nanosheet suspensions by polymer doping. Issue 41 (11th October 2021) - El Rifaii, Karin; Wensink, Henricus H.; Goldmann, Claire; Michot, Laurent; Gabriel, Jean-Christophe P.; Davidson, Patrick
Abstract : Doping a photonic lamellar mesophase of mineral nanosheets with low (resp. high) molecular weight PEO shifts its colour from green to blue (resp. red). Abstract : Aqueous suspensions of nanosheets are readily obtained by exfoliating low-dimensional mineral compounds like H3 Sb3 P2 O14 . The nanosheets self-organize, at low concentration, into a periodic stack of membranes, i.e. a lamellar liquid-crystalline phase. Due to the dilution, this stack has a large period of a few hundred nanometres, it behaves as a 1-dimensional photonic material and displays structural colours. We experimentally investigated the dependence of the period on the nanosheet concentration. We theoretically showed that it cannot be explained by the usual DLVO interaction between uniform lamellae but that the particulate nature of nanosheet-laden membranes must be considered. Moreover, we observed that adding small amounts of 100 kDa poly(ethylene oxide) (PEO) decreases the period and allows tuning the colour throughout the visible range. PEO adsorbs on the nanosheets, inducing a strong reduction of the nanosheet charge. This is probably due to the Lewis-base character of the EO units of PEO that become protonated at the low pH of the system, an interpretation supported by theoretical modeling. Oddly enough, adding small amounts of 1 MDa PEO has the opposite effect of increasing the period, suggesting the presence of an additional intermembrane repulsion not yet identified. From an applied perspective, our work shows how the colours of these 1-dimensional photonic materials can easily be tuned not only by varying the nanosheet concentration (which might entail a phase transition) but also by adding PEO. From a theoretical perspective, our approach represents a necessary step towards establishing the phase diagram of aqueous suspensions of charged nanosheets.